Effect of a High-Protein Diet versus Standard-Protein Diet on Weight Loss and Biomarkers of Metabolic Syndrome: A Randomized Clinical Trial - Ismael Campos-Nonato; Lucia Hernandez; Simon Barquera (Obesity Facts, 2017)
Background: Some studies have shown that protein-enriched diets can lead to greater weight loss and improvements in biomarkers of metabolic syndrome (MeS) than standard protein diets. Therefore, the aim of this study was to determine the effect of increased protein intake on weight loss in Mexican adults with MeS. Methods: Randomized controlled trial in 118 adults aged 47.4 ± 11.5 years and meeting the established criteria for MeS were randomized to prescribed hypocaloric diets (500 kcal less than resting metabolic rate) providing either 0.8 g/kg body weight (standard protein diet (SPD)) or 1.34 g/kg body weight (higher protein diet (HPD)) for 6 months. Body weight, waist circumference, percent body fat by bioimpedance analysis, fasting blood glucose, fasting insulin, hemoglobin A1c, total cholesterol, high-density lipoprotein (HDL) cholesterol, very-low-density lipoprotein (VLDL) cholesterol, triglycerides, C-reactive protein, creatinine, blood urea nitrogen, alanine aminotransferase, aspartate aminotransferase, and gamma-glutamyl transferase were measured at baseline, 3 months and at 6 months. Results: There were 105 subjects (51 for SPD and 54 for HPD) who completed the trial. Overall weight loss was 5.1 ± 3.6 kg in the SPD group compared to 7.0 ± 3.7 kg in the in HPD group. Both groups lost a significant percent of centimeters of waist circumference (SPD -6.5 ± 2.6 cm and HPD -8.8 ± 2.6 cm). There was no statistical difference Except for the varying weight losses the two groups did not show any further differences overall. However in the subgroup judged to be adherent more than 75% of the time with the prescribed diets, there was a significant difference in mean weight loss (SPD -5.8% vs. HPD -9.5%) after adjusting for baseline BMI. Both groups demonstrated significant decreases in waist circumference, glucose, insulin, triglycerides, and VLDL cholesterol, but there were no differences between the groups. There were no changes in blood tests for liver or renal function. Conclusions: There were no significant differences in weight loss and biomarkers of MeS when the overall group was examined, but the participants with more adherence rate in the HPD group lost significantly more weight than adherent participants in the SPD group.